Título Padrão: Registro de Leptochela papulata Chace Jr., 1976 (Crustacea, Decapoda), no litoral brasileiro - Alves Coelho Filho, Petrônio (Arquivos de Ciências do Mar, 2022)
The caridean shrimp Leptochela (Leptochela) papulata (Pasiphaeidae) is recorded for the first time in Brazil based on samples taken with rectangular drag in the coast of the Rio Grande do Norte state (northeastern coast of Brazil). Keywords: Caridea, Potiguar Basin, marine fauna, Western Atlantic.